The Persimmon 9-lipoxygenase Gene DkLOX3 Plays Positive Roles in Both Promoting Senescence and Enhancing Tolerance to Abiotic Stress - Hou, Yali; Meng, Kun; Han, Ye; Ban, Qiuyan; Wang, Biao; Suo, Jiangtao; Lv, Jingyi; Rao, Jingping (Frontiers in Plant Science, 2015)
The lipoxygenase (LOX) pathway is a key regulator for lipid peroxidation, which is crucial for plant senescence and defence pathways. In this study, the transcriptional expression patterns of three persimmon (Diospyros kaki L. ‘Fupingjianshi’) 9-lipoxygenase genes (DkLOX1, DkLOX3 and DkLOX4) were investigated. DkLOX1 was specifically expressed in fruit, particularly in young fruit, and showed little response to the postharvest environments. DkLOX4 was expressed in all tissues and slightly stimulated by mechanical damage and low temperature. DkLOX3 was expressed mainly in mature fruit, and the expression was extremely high throughout the storage period, apparently up-regulated by mechanical damage and high carbon dioxide treatments. Further functional analysis showed that overexpression of DkLOX3 in tomato (Solanum lycopersicum cv. Micro-Tom) accelerated fruit ripening and softening. This was accompanied by higher MDA content and lycopene accumulation, advanced ethylene release peak and elevated expression of ethylene synthesis genes, including ACS2, ACO1 and ACO3. In addition, DkLOX3 overexpression promoted dark induced transgenic Arabidopsis leaf senescence with more chlorophyll loss, increased electrolyte leakage and MDA content. Furthermore, the functions of DkLOX3 in response to abiotic stresses, including osmotic stress, high salinity and drought were investigated. Arabidopsis DkLOX3-OX transgenic lines were found to be more tolerant to osmotic stress with higher germination rate and root growth than wild-type. Moreover, DkLOX3-OX Arabidopsis plants also exhibited enhanced resistance to high salinity and drought, with similar decreased O2- and H2O2 accumulation and upregulation of stress-responsive genes expression, including RD22, RD29A, RD29B and NCED3, except for FRY1, which plays a negative role in stress response. Overall, these results suggested that DkLOX3 plays positive roles both in promoting ripening and senescence through lipid peroxidation and accelerated ethylene production and in stress response via regulating ROS accumulation and stress responsive genes expression.